Catch and discardfish species of trawl fisheries in the Iskenderun Bay (Northeastern Mediterranean) with emphasis on lessepsian and chondricthyan species - YEMISKEN, E.; DALYAN, C.; ERYILMAZ, L. (Mediterranean Marine Science, 2014)
Fish species in catch and discard of trawl fisheries in and around Iskenderun Bay were examined within the fishing closure period and fishingperiod.The sampling was performed from May 2010 to January 2011 by a commercial trawl vessel.Chondricthyan species composed 49 % of discard catch biomass whileGymnura altavela and Dasyatis pastinacawere dominant in hauls. 27 lessepsian fish species were captured during the study,nine of them beingtarget species for trawl fisheries. In total, 14 of the lessepsian fish species were determined as discard species.In both sampling periods, Equulites klunzingeriand Citharus linguatula contributed to discard fish catch dissimilarity among depth ranges (deeper and shallower than 60 m). E. klunzingerishowed high abundance in discard catch.There were no significant differences in the distribution of the discard fish biomass between the sampling periods (ANOVA test, p>0.05). However, depth range pointed out significantdifferences in discard fish catch composition (p<0.05).Among major commercial fish species of trawl fisheries, Mullus surmuletus and Sparus aurata were not separated as discard in anyhaul by fishermen. Any size of these two species were included in commercial catch (Total length ranged from 61 to 721 mm).